Structure and stability of MnOx-Na2WO4/SiO2 catalyst for oxidative condensation of methane - Sevinj Osmanova; Gunel Azimova; Sima Zulfugarova; Etibar Ismailov; Dilgam Taghiyev; Joris Thybaut (Хімія, фізика та технологія поверхні)
Samples of MnOx-Na2WO4/SiO2 based on a mesoporous silica matrix were synthesized using manganese acetate, sodium tungstate, tetraethoxysilane (TEOS) as precursors and cetyltrimethylammonium bromide (CTAB), citric acid and triethanolamine as pore generating agent and characterized by scanning electron microscopy with energy dispersive elemental analysis (SEM/EDS), X-ray diffractometry (XRD), electron magnetic resonance (EMR), N2 adsorption-desorption measurements and tested as a catalyst for the reaction of oxidative condensation of methane (OCM). It is shown that the MnNaW/SiO2 catalyst consists of Mn2O3, MnO2, Na2WO4 and SiO2 phases. The EMR and SEM/EDS data indicate a noticeable effect of the reaction conditions on the surface structure and the distribution of catalytically active components in the catalyst structure. Significant changes in the values of the specific surface area and pore volume of the samples with increasing temperature and duration of the reaction were found (the values of the specific surface area and pore volume, respectively, 116.8 m2/g and 0.590 cm3/g - up to and 46.1 m2/g and 0.232 cm3/g after 15 hours of catalyst operation in the OCM reaction at 800 °C). It has been shown that under the conditions of the OCM reaction, the elemental composition of the surface of the MnOx-Na2WO4/SiO2 catalyst changes, and the degree of change depends on the duration of the OCM reaction. Under the influence of the reaction mixture CH4/O2, the content of Mn and W decreases in the first two hours, and the trend towards a decrease in their amount on the catalyst surface with an increase in the duration of the OCM reaction is generally preserved. A detailed X-ray phase analysis also indicates a change in the phase composition of this catalyst under the influence of the CH4/O2 reaction mixture. It is assumed that under the reaction conditions (700–800 °C) the MnOx-Na2WO4/SiO2 catalyst is silicon dioxide particles basely with the cristabolite structure, the surface of which is coated with molten sodium tungstate containing nanosized particles of MnOx structures activated by sodium ions and WOx.